2017
DOI: 10.1371/journal.pone.0173207
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of three species of Tipuloidea (Diptera, Tipulomorpha) and implications for phylogeny of Tipulomorpha

Abstract: Tipulomorpha has long been a problematic taxon in terms of familial composition, phylogenetic relationships among families and position relative to other ‘lower’ Diptera. Whole-transcriptome shotgun sequencing provides a powerful basis for phylogenetic studies. We performed de novo transcriptome sequencing to produce the first transcriptome datasets representing the families Pediciidae, Limoniidae and Cylindrotomidae using high-throughput sequencing technologies. We assembled cDNA libraries for Pedicia vetusta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The phylogenetic tree in our study (Figure 1) indicated that the Pediciidae was sister-group to the remaining Tipuloidea, which was accepted by Ribeiro (2008), Petersen et al (2010) and Kang et al (2017). Our phylogenetic analysis also showed a strong support for the sister-group relationship between Cylindrotomidae and Tipulidae.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The phylogenetic tree in our study (Figure 1) indicated that the Pediciidae was sister-group to the remaining Tipuloidea, which was accepted by Ribeiro (2008), Petersen et al (2010) and Kang et al (2017). Our phylogenetic analysis also showed a strong support for the sister-group relationship between Cylindrotomidae and Tipulidae.…”
supporting
confidence: 66%
“…( 2010 ) and Kang et al. ( 2017 ). Our phylogenetic analysis also showed a strong support for the sister-group relationship between Cylindrotomidae and Tipulidae.…”
mentioning
confidence: 96%
“…The value of the more than a 100‐fold expansion of gene coverage for entomological phylogenomic studies is evident (e.g. Niehuis et al ., ; Letsch & Simon, ; Misof et al ., ; Kang et al ., ; Bazinet et al ., ; Peters et al ., ). For example, the once controversial monophyly of Polyneoptera and positions therein of Strepsiptera as sister to Coleoptera and Hymenoptera as sister group to ‘Aparaglossata’ have become widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of RNA-seq data in P. alba have identified a total of 39,000 unique singletons that would potentially contribute to the population-based genome studies in the genera (Torales et al 2013). Kang et al obtained 1709 single-copy orthologs genes from analyzed species through RNA-seq data analyses and four-cluster likelihood mapping was used to study potential incongruent signals (Kang et al 2017).…”
Section: Prosopis Albamentioning
confidence: 99%